2009
DOI: 10.1002/ejic.200900516
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structures, Spectroscopic Properties, and Catalytic Aerobic Oxidations of Novel Trinuclear Non‐Heme Iron Complexes

Abstract: Keywords: Carboxylate ligands / EPR spectroscopy / EXAFS spectroscopy / Mössbauer spectroscopy / OxidationA series of 2,6-diacylpyridine ligand precursors 5a-d·HCl with different tether lengths between the carboxyl and pyridine moiety was prepared and converted into the correspondig trinuclear Fe 3 (µ 3 -O) complexes 8a-d and 10. Under slow precipitation conditions a tetranuclear complex 9 was isolated instead of 8a. Single-crystal X-ray diffraction analyses were performed on ligands 5a-d and complexes 9 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 104 publications
1
20
0
Order By: Relevance
“…Unfortunately, X-ray crystal structures of the complexes 3a and 3c -3e could not be obtained. However, spectroscopic and analytical data (ESI-MS, IR, and elemental analysis) were in good agreement with our previously reported [Fe 3 (m 3 -O)] complex 3f (R ¼ H) [24].…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Unfortunately, X-ray crystal structures of the complexes 3a and 3c -3e could not be obtained. However, spectroscopic and analytical data (ESI-MS, IR, and elemental analysis) were in good agreement with our previously reported [Fe 3 (m 3 -O)] complex 3f (R ¼ H) [24].…”
supporting
confidence: 84%
“…In particular, the tether length had no influence on the nuclearity of the Fe complex. Furthermore, during catalytic aerobic oxidation, freeze-quench Mçssbauer and nuclear inelastic scattering data revealed that the precursor complexes 2 and 3 undergo cleavage to mononuclear species [24] [25], which is in agreement with Bartons original proposal of the catalytic cycle [21b]. We thus anticipated that substituents at C(4) of the pyridine reaction progress must be carefully monitored, and the reactions have to be stopped at incomplete conversion in order to avoid overreduction.…”
mentioning
confidence: 55%
See 3 more Smart Citations